Receptor Guanylyl Cyclase C and Cyclic GMP in Health and Disease: Perspectives and Therapeutic Opportunities - Prasad, Hari; Mathew, John Kandam Kulathu; Visweswariah, Sandhya S. (Frontiers in Endocrinology, 2022)
Receptor Guanylyl Cyclase C (GC-C) was initially characterized as an important regulator of intestinal fluid and ion homeostasis. Recent findings demonstrate that GC-C is also causally linked to intestinal inflammation, dysbiosis, and tumorigenesis. These advances have been fueled in part by identifying mutations or changes in gene expression in GC-C or its ligands, that disrupt the delicate balance of intracellular cGMP levels and are associated with a wide range of clinical phenotypes. In this review, we highlight aspects of the current knowledge of the GC-C signaling pathway in homeostasis and disease, emphasizing recent advances in the field. The review summarizes extra gastrointestinal functions for GC-C signaling, such as appetite control, energy expenditure, visceral nociception, and behavioral processes. Recent research has expanded the homeostatic role of GC-C and implicated it in regulating the ion-microbiome-immune axis, which acts as a mechanistic driver in inflammatory bowel disease. The development of transgenic and knockout mouse models allowed for in-depth studies of GC-C and its relationship to whole-animal physiology. A deeper understanding of the various aspects of GC-C biology and their relationships with pathologies such as inflammatory bowel disease, colorectal cancer, and obesity can be leveraged to devise novel therapeutics.